Evaluation of a newly developed chemiluminescence immunoassay for detecting cardiac troponin T. Issue 3 (22nd September 2017) - Wang, Jingkun; Fang, Yizhen; Li, Peihua; Lin, Huayue; Jin, Hongwei; Gao, Lei; Ge, Shengxiang; Zhang, Zhong‐Ying
Abstract : Background: To evaluate the performance of a chemiluminescence detection kit for cardiac troponin T (cTnT). Methods: According to the "Guiding principles on performance analysis of diagnostic reagents in vitro" and the Clinical and Laboratory Standards Institute (CLSI) Guidelines, we assessed the detection limit, linear range, reportable range, accuracy, precision, cross reactivity, interference factors, and matrix effect of the kit, and compared these parameters with that of the commercial electrochemiluminescence detection kit for cTnT (Roche). Results: The minimum detection limit of the kit was 0.01 ng/mL. The linear range was 0.01 ng/mL‐25 ng/mL. The reportable range was from 0.01 ng/mL to 100 ng/mL. Precision within the batch was 2.9%‐6.4%, and precision between batches was 6.0%; the accuracy was good and the recovery rate reached 96.2%. The cross‐reaction test demonstrated that there was no reactivity between cTnT and a variety of troponins. Test results deviated by less than ±10% in the presence of hemoglobin ≤1000 μg/mL, bilirubin ≤250 μg/mL, triglycerides ≤11.25 mg/mL, and rheumatoid factor ≤206 U/mL, suggesting that kit results were not significantly interfered with these factors. Results from the matrix‐effect assessment revealed absence of a matrix effect in the tested serum samples. Correlation study revealed that the performance of the kit was very consistent with that of the Roche electrochemiluminescence detection kit (Kappa = 0.900, P < .001) with a high correlation ( r = .903, P < .001) and a total matching rate of 95.00%. Conclusion: The performance of the evaluated chemiluminescence immunoquantitation kit for cTnT detection was acceptable in all tested parameters, fulfilling requirements for clinical applications.